2015
DOI: 10.1177/0095244315576244
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis of rigid polyurethane–polyisocyanurate foams with reduced flammability

Abstract: Waste of foam containing tri( N, N ′-dimethyleneoxy-3-hydroxypropyl)urea as a polyol was subjected to glycolysis process. After glycolysis, a liquid tea-coloured product, with high viscosity of 17,040 mPa·S, density of 1529 kg/m3, water content of 0.4% and boron and nitrogen content of about 14%, was obtained. New rigid polyurethane–polyisocyanurate foams containing glycolysis product of foam waste with reduced flammability were obtained. It was used as a polyol raw material, simultaneously fulfilling the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…The results indicated that adequate concentrations of diethylene glycol (DEG) and potassium acetate (KAc) are about 150% and 1% of the mass of the PU, respectively, and an adequate reaction time is 90 min, but purification of the glycolysis products was necessary. Joanna Paciorek-Sadowska et al [ 172 ] recycled rigid PUFs and rigid PU–polyisocyanurate foams by glycolysis. Afterwards, foams containing the glycolysis product were produced, which presented better flammability properties.…”
Section: Strategies Toward the Sustainability Of Pufsmentioning
confidence: 99%
“…The results indicated that adequate concentrations of diethylene glycol (DEG) and potassium acetate (KAc) are about 150% and 1% of the mass of the PU, respectively, and an adequate reaction time is 90 min, but purification of the glycolysis products was necessary. Joanna Paciorek-Sadowska et al [ 172 ] recycled rigid PUFs and rigid PU–polyisocyanurate foams by glycolysis. Afterwards, foams containing the glycolysis product were produced, which presented better flammability properties.…”
Section: Strategies Toward the Sustainability Of Pufsmentioning
confidence: 99%
“…A. König studied the effect of the new flame retardant methyl-DOPO properties on FPUF. Also, the flame retardant property of rigid polyurethane foams (RPUF) was studied widely [7][8][9][10][11][12]. In these years, however, semirigid polyurethane foam (SPUF) is generally used in various fields, such as leather processing, textile printing, paper-making industry, architectural coatings, adhesives, and cushioning materials.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, taking into account the fact that the used polyol was obtained as a result of chemical recycling of waste meant that these values are indeed high. In general, polyol raw material from the glycolysis process, which was used for the production of PU materials, resulted in the creation of foams with a compressive strength well below the 300 kPa value [39,40].…”
Section: Resultsmentioning
confidence: 99%
“…The difference was in the mass loss value. Foams based on biopolyols and PU glycolysates showed a downward trend of this parameter [28,35,40]. This is due to the presence of thermally resistant molecules from vegetable oils (in biopolyols) and complex structures containing hard segments of polyurethane (in PU glycolysates).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation